ANALISIS DIMENSI KEWARGAAN SISWA SEKOLAH DASAR DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI LINGKUNGAN MULTIKULTURAL - sarbaini, Weni; Abd Aziz Tambunan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The citizenship dimension is a fundamental basis for developing students who respect diversity, act responsibly, and participate in collective life. However, in multicultural school settings, its enactment through Pancasila Education is not always consistent, particularly in the use of students’ cultural experiences and respect for peers’ personal boundaries. This study aimed to analyze the manifestation of the citizenship dimension among primary school students, teachers’ strategies for integrating cultural diversity, and the supporting and inhibiting factors in its development. This qualitative case study was conducted in a fourth-grade class at an elementary school in Medan, Indonesia. The class consisted of 30 students, while the 16 informants comprised 14 students, one classroom teacher, and one principal. Seven students participated in a focus group discussion, while seven others took part in in-depth interviews. Data were collected through three classroom observations, semi-structured interviews, a focus group discussion, and document analysis, and were analyzed thematically. The findings showed that the citizenship dimension was manifested through active participation, cooperation, responsibility, expression of opinions, and compliance with classroom agreements. However, cultural diversity had not been systematically utilized as a learning context, while the use of nicknames perceived as joking could cause discomfort. Teacher guidance, attitude assessment, school rules, and habituation activities supported citizenship development, whereas limited cultural integration, uneven self-confidence, and insufficient multicultural activities remained inhibiting factors. Pancasila Education therefore needs to integrate students’ cultural experiences, reflective dialogue, empathy, respectful communication, and citizenship assessment more consistently.